Challenges, Choices and Change: Towards a Theoretical Model of African Diasporan Women’s Educational Decision Making - Carmela R. Nanton (Adult Education Research Conference, 2006)
The decision to participate in adult learning programs is often triggered by life-challenges. The choice for this diverse sample of African diasporan women was adult learning. Components of the decision process, the relationship to ego development level, and resulting changes are examined and a proposed theoretical model is discussed.
Keywords: Decision process; African Diaspora